CONSTRUINDO BRINQUEDOTECAS: APRENDER RECICLANDO, RECICLAR PRESERVANDO - TONEL, CRISTINA P.; GREZCA, FRANCINI C.; ZORZAN, GIOSELI; ROSLER, LUCIANA; BOZZETTO, INGRIDE (Salão do Conhecimento, 2013)
Resumo